170kW Solar Power Plant Microgrid in the Remote Island Indonesia: An overview - Andrianshah Priyadi; Toha Zaky; Riza riza (JAREE (Journal on Advanced Research in Electrical Engineering), 2018)
Indonesia is the largest archipelagic country in the world consisting of 17,508 islands including 9,638 unnamed islands and 6,000 uninhabited islands. The population which increases every year showing the results that there is the migration of people from the large islands to the remote islands and one of the problems of this condition is the optimal electricity supply. Electricity on the island is commonly carried out by diesel engines, so it needed combining the power plant system that reduced the working-load of diesel engines. One of the power plants is a solar power plant which needed to support the government's National Energy Policy (NEP) program in renewable energy. The paper has done by assessing one of the remote islands in Indonesia by identifying the whole power plant system design. The total number of solar power plant capacity installed is 170 kWp and 3 x 240 kW diesel engine. In the Future plan, the project will be made of a Solar Power Plant system that is reliable as a smart grid system and also there is optimizing in the load design. The paper will also identify all possibilities technical aspect that could improve the system becomes a smart grid system in the future. Keywords: Microgrid, Smartgrid, Solar Power Plant, Renewable Energy